EFFECT OF WELFARE SCHEME ON EMPLOYEE’S JOB SATISFACTION IN SELECTED RESEARCH INSTITUTE OF SOUTHWEST, NIGERIA - Abiona Grace BOLAJI; Ajayi OLAYEMI (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The study determine the effect of welfare scheme on employee’s job satisfaction in Cocoa and Forest Research Institute of Nigeria, Southwest, Nigeria. Three hundred and twenty five employees were selected through simple random sampling techniques with the use of interviewed guide. Data collected were analysed using different statistical tools. Results revealed that the mean age of the employees was 38years, more than half (56.4%) of the employees were male, 32.9% and 52.1% were married. The result also revealed major welfare services as flexibility of work schedule (